The Influence Of Occupational Health Safety (K3) And Work Environment On Employee Performance At PT. Tri Kemasindo Lestari Cakung East Jakarta - Brenda Arim Melati; Jonny Siagian; Nenny Anggraini (Fundamental Management Journal, 2023)
BRENDA ARIM MELATI, The Effect of Occupational Health, Safety and Work Environment on the Performance of PT Tri Kemasindo Lestari Employees Human resources have the meaning that labor or employees are needed and are the things that play the most important role in making profits, goods and services for the company. Therefore, it is very important from the company to pay attention to the safety and health of the workers because it greatly affects the success of the company itself, if the company does not control the safety and health of the workers it will be fatal both in terms of company performance and in terms of the workforce. alone, On the other hand, there are also factors from the work environment that the company is not paying attention to at this time. employees themselves, therefore the company must prepare adequate working environment conditions. The type of data used in this study is quantitative data, and the data analysis used is re with the number of samples in this study is 30 people. The data collection method used is a questionnaire with a measurement scale using a Likert scale. All data in this study were processed using SPSS 25 for Windows. Suggestion: It is expected that the company will always pay attention to the health and safety of employees, such as providing protective head hats for employees who work in the transfer of goods, holding counseling on procedures for using production equipment safely, providing medical clinics for workers who have work accidents, providing gloves or other means to protect workers. The company is expected to pay attention to the work space for workers, which must have adequate temperature, air circulation, and lighting, provide new innovations in the workspace so that it can provide comfort for workers, pay attention to environmental cleanliness for employee comfort. Keywords: occupational health safety, work environment, employee performance